Pengaruh Disiplin Terhadap Produktivitas dan Efektivitas Kinerja ASN di Dinas Tenaga Kerja dan Perindustrian Kota Padang - Iskandar, Mhd. Fadhel Adli; Syahputra, M. Akhir; Ramadani, Zahara; Hanoselina, Yulia (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
This study aims to analyze the effect of work discipline on the productivity and effectiveness of the performance of State Civil Apparatus (ASN) at the Padang City Manpower and Industry Service. The method used in this study is the literature review method or an approach that uses relevant literature sources or written documents. In addition, the data collection techniques used in this study are observation, interviews, and documentation. The results of the study indicate that work discipline has a significant positive impact on the productivity and effectiveness of ASN performance. The results of interviews at the Padang City Manpower and Industry Service indicate that ASN are required to comply with rules such as arriving on time, with an automatic allowance deduction mechanism for those who are late. Even though there is a strict policy like this, challenges in implementing discipline remain, for example in terms of employee consistency in arriving on time. To overcome this, the sub-section head provides a five-minute lateness dispensation, and the results are quite low with the allowance deduction system applied. These findings are expected to be used as consideration in improving ASN performance through the implementation of stricter disciplinary policies.